2009
DOI: 10.1387/ijdb.082742cs
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence against a role for W-linked histidine triad nucleotide binding protein (HINTW) in avian sex determination

Abstract: Birds have a ZZ/ZW sex chromosome system, but the mechanism of sex determination remains unknown. The heterogametic sex is female (ZW) and one hypothesis holds that the W chromosome carries a dominant-acting ovary-determining gene. The strongest candidate ovary-determinant on the W chromosome is HINTW, which encodes an aberrant nucleotide hydrolase enzyme. HINTW is conserved amongst all carinate (flying) birds and it is strongly expressed in the gonads and other tissues of female chicken embryos. This and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 46 publications
3
38
0
1
Order By: Relevance
“…In vitro enzyme data support a dominant negative influence of HINTW on HINTZ enzymatic activity (Parks et al 2004). However, the HINTW gene is apparently absent in ratites, and overexpression in early Chicken embryos does not induce ovarian development, undermining this gene as a candidate female determinant (Smith et al 2009b). At present, therefore, there is little evidence in support of the dominant W hypothesis for avian sex determination.…”
Section: Does the W Sex Chromosome Participate In Avian Sex Determinamentioning
confidence: 93%
“…In vitro enzyme data support a dominant negative influence of HINTW on HINTZ enzymatic activity (Parks et al 2004). However, the HINTW gene is apparently absent in ratites, and overexpression in early Chicken embryos does not induce ovarian development, undermining this gene as a candidate female determinant (Smith et al 2009b). At present, therefore, there is little evidence in support of the dominant W hypothesis for avian sex determination.…”
Section: Does the W Sex Chromosome Participate In Avian Sex Determinamentioning
confidence: 93%
“…At an early stage, DMRT1 (Raymond et al, 1999;Oreal et al, 2002;Smith et al, 2003;Yamamoto et al, 2003;Koba et al, 2008;Smith et al, 2009b;Yang et al, 2013) and Sox9 (Kent et al, 1996;Morais da Silva et al, 1996;Yamamoto et al, 2003;Takada et al, 2006) are expressed in male (ZZ) embryos, whereas HINTW (Smith, 2007;Smith et al, 2009a), FET1 (Reed and Sinclair, 2002), FOXL2 (Hudson et al, 2005b) and aromatase Nakabayashi et al, 1998;Yamamoto et al, 2003) are expressed in female (ZW) embryos.…”
Section: Asymmetric Gene Expression In Female and Male Embryonic Gonadsmentioning
confidence: 99%
“…Viral titer was assessed by adding serial dilutions (10 -3 -10 -8 ) of concentrated virus to the fresh DF-1 cells as described previously [Logan and Tabin, 1998;Smith et al, 2009b]. DF-1 cells were infected with RCASBP.B-SMARCE1 virus and harvested several days later.…”
Section: Infection Of Df-1 Cellsmentioning
confidence: 99%
“…Among them, DMRT1 was found to be required for testis determination in chicken [Smith et al, 2009a], while PKCIW did not play a dominant role in avian sex determination [Smith et al, 2009b]. The last candidate FET1 was once considered to be a unique ovary-determining gene because no counterpart on the Z chromosome was reported, although our experiments (unpublished result) found several homologs on the Z chromosome which had an identity of 91% with FET1 , which indicated that FET1 might not be so unique in avian sex determination.…”
mentioning
confidence: 98%